Bone, Mattompang Arajang, ‘Kayu Galadupa’ (Sindora galedupa; Fabaceae) dan Jejaring Bugis Nusantara - Ary Prihardhyanto Keim; Muhamad Nikmatullah; Nissa Arifa; Tukul Rameyo Adi; Wardah Wardah; Wawan Sujarwo (The Ethnobiological Society of Indonesia, 2020)
The result of this current study shows that Bone as the centre of origin of the Bugisnese civilization is still preserving most of the original tradition alive like the Mattompang Arajang procession, which is now connected with the Anniversary of the City of Watampone, the capital of Bone Regency. Mattompang Arajang procession involves an important component, which is burning the incense. In the past, the incense burned was the indigenous Sulawesi incense known as ‘kayu Galadupa’ (thus the name of the resin is ‘Kemenyan Galadupa’ or Galadupa incense), which is identified here as the resin harvested from Sindora galedupa (Fabaceae). The species is very rarely seen in the forest now and this gave impact to the production of the resin. The Galadupa incense has not been used for many years and slowly forgotten and replaced by the more common Sumatran incense harvested from Styrax benzoin or S. sumatrana (Styracaceae). The Mattompang Arajang yearly procession also acts as a uniting moment for Bugisnese descents throughout Nusantara (i.e. Malay Archipelago and beyond). The prospect of creating a Nusantara Bugisnese Networking is also discussed. In connection with the Mattompang Arajang procession, as the procession is regarded deeply rooted in the Bugisnese existence, the indigenous incense should have been implemented and preserved. This is good news for the conservation of the Galadupa tree, Sindora galedupa in its own homeland.